Examination Of The Relationship between Family Care, Organizational Support, and Health Professionals’ Quality of Life - Ismail , Moamen Abdelfadil; Ismail , Moamen Abdelfadil; Ismail , Moamen Abdelfadil; Almuhanna , Abdullah Sulaiman; ALBUGAMI, FAISAL KHALED; Alhabib, Kalid ali; Farahat, Yara Hany; Aldablan, Abdulrahman Saud; AlDhamen , Khlood Salman; Al-Wadani, Mohammed Salem Jaber; BAZ, Rawhiyyah Mansur Abdullah; Alsoraya, Bayan Mohammed; et al. (Journal of Ecohumanism, 2024)
Background: Professional quality of life (ProQOL) encompasses the well-being of healthcare professionals, including compassion satisfaction, burnout, and secondary trauma. While research on ProQOL has expanded, limited attention has been given to the influence of family care and organizational support on nurses’ work experiences. This study aims to assess the impact of family care and organizational support on the three dimensions of ProQOL among clinical nurses. Methods: A cross-sectional study was conducted using a structured questionnaire administered to 1,700 nurses. The survey collected demographic data and utilized validated scales, including the Family Care Scale, Professional Quality of Life Scale (ProQOL), Organizational Support Scale, and Work-Family Conflict Scale. Multiple stepwise regression analyses were performed to examine the relationships between family care, organizational support, and ProQOL dimensions. Results: The findings demonstrated that family care, organizational support, and work-family conflict were significantly associated with all three ProQOL dimensions (P < 0.05). Higher levels of family care and organizational support were positively correlated with compassion satisfaction and negatively correlated with burnout and secondary trauma. Work-family conflict exhibited an inverse relationship with ProQOL, contributing to increased burnout and secondary trauma. Nurses who reported stronger family care and greater organizational support experienced higher professional well-being. Conclusion: This study underscores the crucial role of family care and organizational support in shaping nurses’ professional quality of life. Healthcare institutions should implement targeted strategies to enhance organizational support, reduce work-family conflict, and foster a supportive work environment. By addressing these factors, nursing administrators can improve job satisfaction, reduce burnout, and enhance overall professional well-being among clinical nurses